Cognition is associated with daily-life mobility in people with Parkinson’s disease - Burgos, Pablo I.; Silva-Batista, Carla; Ragothaman, Anjanibhargavi; Shah, Vrutangkumar V.; Carlson-Kuhta, Patricia; Horak, Fay B.; Mancini, Martina (Clinical parkinsonism & related disorders, 2025)
•People with PD with poor visuospatial abilities walked slower and with shorter strides.•People with PD with poor executive function had longer double support time.•Poor executive function was also associated with reduced variability in turning performance.•Disease duration and age had a stronger influence on the relationship between cognition and mobility than FoG status. Cognitive impairment is common in people with Parkinson’s disease (PD). Mobility is also impaired in people with PD and functional mobility often requires cognitive dual-tasking to navigate complex environments in daily life. We hypothesized that visuospatial and executive cognitive dysfunction in people with PD will be associated with digital measures of mobility in daily life. Since freezing of gait (FoG) is associated with both cognitive dysfunction and mobility impairments, we also examined the influence of FoG on the cognition-mobility relationship. Here, we investigated, for the first time, the association between cognition and daily-life mobility in PD and the influence of FoG status. 60 individuals with mild-to-moderate PD (17 with FoG and 43 without FoG) wore 3 inertial sensors (lumbar and feet) for a week of passive monitoring of mobility. Digital visuospatial (Line Orientation task) and executive tasks (Set-Shifting and Flanker task) were assessed in the ON medication state. Visuospatial function was significantly associated with gait speed (r = -0.46, p = 0.008) and stride length (r = -0.40, p = 0.022). Set Shifting was significantly associated with stance time (r = -0.35, p = 0.046), double support time (r = -0.35, p = 0.046), and the variability of step duration during turning (r = 0.44, p = 0.016). The Flanker test was not associated with any gait variables. FoG status was less important than disease duration or age in the cognitive-mobility associations. Specific types of cognition were related to specific gait variables in daily life. People with PD with worse visuospatial functions had worse gait pace. In contrast, participants with worse executive function (set-switching) had worse dynamic postural control during gait. FoG status showed minimal influence on these associations.